Mesonephric Like-Carcinoma (MLCA) of the Uterus with a Predominant Spindled Morphology: A Case Report. (28th October 2021) - Ibrahim, E; Sheridan, T; Mandavilli, S
Abstract: Introduction/Objective: Mesonephric-like carcinoma of the uterus is an increasingly recognized carcinoma with mesonephric differentiation, but without association with mesonephric remnants. We present a case of a 60-year-old woman presented with postmenopausal bleeding. Methods/Case Report: Pelvic MRI showed possibly a cervical lobulated lesion (4.4cm) extending into the endocervical canal. Initial biopsy of this mass showed a spindle cell neoplasm raising possibility of an endometrial stromal sarcoma. On subsequent radical hysterectomy, there was a mass arising in the lower uterine segment (LUS) with circumferential cervical involvement. The tumor was comprised of sheets of epithelioid to spindle cells with scant cytoplasm and indistinct cell borders. Abundant mitotic figures and foci of necrosis were identified. Focal areas showed dense sclerosis with cords of cells, and only rare areas showed tubule formation with scant secretions. By immunohistochemistry (IHC), the tumor cells were positive for keratin AE1/AE3 (strong, diffuse), TTF-1, p63, p16, CD10 (with luminal accentuation); PAX8, desmin and caldesmon showed focal/rare positivity. Other markers were negative, including GATA3 (patchy, weak), ER and PR. Mismatch repair proteins were intact. Next-generation sequencing (NGS) revealed a KRAS mutation. Considering strong expression of epithelial markers, focal tubule formation with positive TTF-1 and negative GATA-3 labeling, and absence of identified mesonephric remnants, the tumor was classified as a high-grade mesonephric-like carcinoma of the uterus (LUS). Pelvic lymph nodes were negative (pT2 N0), and the patient is receiving cisplatin and external beam radiation. Results (if a Case Study enter NA): NA Conclusion: MLCA with a prominent spindled/sarcomatoid component can be difficult to diagnose. Ancillary testing including a broad IHC panel with TTF-1, GATA-3 and NGS may be useful to aid in the diagnosis.